The healthy fright of losing a good one for a bad one - Annalisa Cristini; Federica Origo; Sara Pinoli (Institute for the Study of Labor (IZA), 2012)
In this paper we study the effect of different degrees of employment protection on absenteeism, paying attention to differences between workers moving from protected jobs to insecure jobs, on the one hand, and workers moving from insecure to secure jobs, on the other hand. Using a large representative sample of Italian workers, we show that workers' reaction in terms of sickness leave is not symmetric: losing protection (bad news) is more effective than gaining it (good news). We claim that this asymmetry is consistent with the behavior of financial markets responding to good and bad news. In our case, workers react in a more prudential way to improvements in their employment status (wait and see strategy), while they do immediately adjust to worsening job security by showing off healthy behavior.
urn:nbn:de:101:1-201205026140
Keywords: J22; J41; 330; absenteeism; employment protection; delayed reaction; Fehlzeit; Kündigungsschutz; Arbeitsplatzsicherung; Arbeitsverhalten; Italien